Use of Polarised Light Microscopy to Improve Conservation of Parchment. (4th July 2019) - Vilde, Vladimir; Fourneau, Marc; Charles, Catherine; Van Vlaender, Daniel; Bouhy, Julie; Poumay, Yves; Deparis, Olivier
ABSTRACT: The preservation state of parchment primarily depends on the structure of the collagen fibre network, which in turn is responsible for optical anisotropy, i.e. birefringence. Polarised light microscopy can therefore be used as a non-invasive technique that allows recording of birefringence distribution in the parchment, which directly relates to stress–strain distribution. Using samples from diverse sources (commercial parchment, parchment used by restorers for book binding, and parchment fabricated for the purpose of this study), we assessed the capability of polarised light microscopy for various diagnostics. We performed, for instance, identification of gelatinised regions, layered or ﬁbrous regions in parchment cross section, qualitative analysis of parchment fat content (lipids), observation of stress-induced patterns resulting from tensile tests, and observation of water diffusion. These proof-of-principle experiments extend the capability of polarised light microscopy far beyond its common use and open the path to its deployment in conservation studies.